Preparation and characterization activated carbon from rice husk and oil palm empty fruit bunches for removal of Zn2+ in aqueous solution - Ismail, N.E.A. (American Institute of Physics Inc., 2016)
The ability of activated carbon prepared from rice husk (RH), oil palm empty fruit bunches (EFB) and mixture (Mix) activated carbon in adsorption of Zinc (Zn2+) from aqueous solution was investigated. The Mix activated carbon has prepared from mixture of RH and EFB activated carbon with weight ratio (1:1) The RH and EFB activated carbon were produced by using sodium hydroxide (NaOH) as a dehydrating agent in chemical activation process.EFB activated carbon showed excellent efficiency in removing Zn2+ with their percentage removal up to 100 even at low adsorbent dosage. The study also showed that the adsorption of Zn2+ by EFB, RH and Mix activated carbon is dependent on the adsorbent dosage and initial metal concentration. The adsorption isotherms of the Zn2+ of EFB, RH and Mix activated carbon were determined and compared with Langmuir and Freundlich models. It was showed that Langmuir model was more favorable for RH and Mix activated carbon with correlation coefficient (R2) value is 0.9958 and 0.9847. In contrast, EFB activated carbon was more favorable to the Freundlich and Langmuir model with correlation coefficient (R2) are 0.9967 and 0.9967 Â© 2016 Author(s).